Students’ Strategies In Overcoming Translating Barrier - Bimo Jatikusumo; Agus Rofii; Rahma Ilyas (Universitas Majalengka, 2022)
The process of translation is not as easy as it seems. In fact, it is much harder. The translation result must fulfill certain criteria namely accuracy, acceptability, and readability. During the process of translation, the translator surely encounters some difficulties or barrier. Therefore, this study aimed to find out the students’ strategies in overcoming the translation difficulties. The method of the research was a descriptive case-study. The subject of the research was 10 students of English Education Department at Universitas Majalengka. The data was collected from the translation test, questionnaire, and interview. Most of the data analysis of this research was conveyed in non-statistical analysis. However, the researcher provided data to see the percentage and frequencies to support the research. The results showed that the students encounter difficulties in 1) translating words that are not in dictionary; 2) translating ambiguous words; 3) translating long sentences; 4) translating phrases; 5) translating complex sentence; and 6) translating idioms. In translating idioms, 50% used literal translation, 30% used discursive creation, and 20% used established equivalence. In translating ambiguous words, 90% used modulation, and 10 % used literal translation. In translating phrases, 40% used reduction, 20% used discursive creation, 10% used established equivalence, and 30% used generalization.